Nuxcell Neo® improves vaccine efficacy in antibody response - Jesus, Gabriel Fernandes Alves; Galvani, Nathalia Coral; Abel, Jéssica da Silva; Scussel, Rahisa; Fagundes, Mírian ĺvens; Córneo, Emily da Silva; Rossetto, Marina; Sargiani, Debora; de Ávila, Ricardo Andrez Machado; Michels, Monique (Frontiers in Veterinary Science, 2024)
Current vaccination protocols raise concerns about the efficacy of immunization. There is evidence that changes in the gut microbiota can impact immune response. The formation of the gut microbiota in newborns plays a crucial role in immunity. Probiotic bacteria and prebiotics present important health-promoting and immunomodulatory properties. Thus, we hypothesize that pro and prebiotics supplementation can improve the efficacy of vaccination in newborns. In this protocol, newborns mices were used and treated with single-dose rabies vaccine combined with Nuxcell Neo® (2g/animal/week) for 3 weeks. Samples were collected on days 7, 14 and 21 after vaccination for analysis of cytokines and concentration of circulating antibodies. Our results have shown an increased concentration of antibodies in animals vaccinated against rabies and simultaneously treated with Nuxcell Neo® on days 14 and 21 when compared to the group receiving only the vaccine. In the cytokine levels analysis, it was possible to observe that there weren't relevant and significant changes between the groups, which demonstrates that the health of the animal remains stable. The results of our study confirm the promising impact of the use of Nuxcell Neo® on the immune response after vaccination.